Vitamin D receptor polymorphisms are associated with severity of wheezing illnesses and asthma exacerbations in children. Issue 201 (July 2020) - Leiter, Katharine; Franks, Kimberley; Borland, Meredith L; Coleman, Laura; Harris, Leesa; Le Souëf, Peter N.; Laing, Ingrid A.
Highlights: Vitamin D receptor polymorphisms may play a role in acute wheeze/asthma severity in children. A likely relationship has been identified between the rs2525046 genotype and VDR mRNA intensity levels. The VDR rs2228570 AA genotype is associated with higher exacerbation severity scores and poorer treatment response. Abstract: Single nucleotide polymorphisms (SNPs) of the vitamin D receptor ( VDR ) gene have shown linkage and association with asthma development in multiple cohort studies. However, the majority of investigations have focused on asthma phenotypes in cohorts with stable disease. We investigated the relationship between VDR SNPs and the frequency and severity of acute episodes of wheeze/asthma in a cohort of Australian children, as the ability to identify children at risk of more severe exacerbations could lead to personalized and improved genotype-specific treatment pathways. We successfully genotyped five SNPs of the VDR gene (rs2525046, rs9729, rs1544410 ( Bsm I), rs22239179, and rs2228570 ( Fok I)) in 657 children presenting to a tertiary children's hospital with acute asthma, bronchiolitis, or a wheezing illness. The relationships between VDR SNPs and exacerbation severity scores, β2 -agonist use, and frequency of respiratory exacerbations were analysed using multiple regression. The rs2525046 ( Fok I) CT genotype was associated with higher VDR mRNA intensity levels ( p = 0.007) compared to the CC genotype. A trend towards significance ( p =0.056) was identified between the rs2525046 TT genotype and higher VDR mRNA intensity levels compared to the CC genotype. Children with rs2228570 AA genotype had higher exacerbation severity scores ( p =0.001) and poorer β2 -agonist treatment response (doses at 6 h: p = 0.009 and 12 h: p =0.033) compared to those with the GG genotype. Children with rs1544410 ( Bsm I) TT genotype had lower exacerbation severity scores ( p = 0.005) compared to those with the CC genotype. Children with rs2228570 GA genotype presented to and/or were admitted to hospital more times since birth with respiratory ( p = 0.011) and wheezing ( p = 0.021) illnesses than children with the GG genotype. No associations were identified between rs9729, rs2525046 and r2239179 polymorphisms and acute wheezing/asthma variables. These findings suggest that genetic variants at the VDR locus may play a role in acute wheeze/asthma severity in children.